A critical role of Lyn and Fyn for B cell responses to CD38 ligation and interleukin 5 - Yasue, Tokutaro (The National Academy of Sciences of the USA, 1997)
CD38 ligation on mouse B cells by CS/2, an anti-mouse CD38 mAb, induced proliferation, interleukin 5 (IL-5) receptor α chain expression, and tyrosine phosphorylation of Bruton tyrosine kinase (Btk) from wild-type, but not from X chromosome-linked, immunodeficient mice. B cells from fyn-deficient (Fyn(−/−)) and lyn-deficient (Lyn(−/−)) mice showed an impaired response to mAb CS/2 for proliferation and IL-5 receptor α chain expression, and B cells from fyn/lyn double-deficient (Fyn/Lyn(−/−)) mice did not respond at all to mAb CS/2. The Btk activation by CD38 ligation was observed in B cells from Fyn(−/−) mice, and it was severely impaired in B cells from Lyn(−/−) and Fyn/Lyn(−/−) mice. CD38 expression on B cells from three mutant strains was comparable to that on control B cells. We infer from these results that both Fyn and Lyn are required and that their signals are synergistic for B cell triggering after CD38 ligation. Lyn is upstream of Btk activation in the CD38 signaling. Stimulation of B cells with IL-5 together with CD38 ligation induces not only IgM but also IgG1 secretion. Analysis of the synergistic effects of IL-5 and CD38 ligation on IgG1 secretion revealed the impaired IgG1 secretion of B cells from Lyn(−/−) and Fyn/Lyn(−/−) mice. These data imply that Lyn is involved in B cell triggering by CD38 ligation plus IL-5 for isotype switching.